Ab initio modeling of the amorphization process in a Fe−Zr system - Plyushchay, I. V.; Makara, V. A.; Plyushchay, A. I.; Volkova, T. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Ab initio molecular dynamics simulations of the amorphization process in a Fe−Zr system have been presented. The atomic positions in the Fe29Zr3 supercell are modeled by simulating the annealing by the density functional theory in the generalized gradient approximation. Changes in the density of electronic states of the Fe29Zr3 supercell under crystalline-liquid-amorphous phase transitions are discussed. The most marked difference between the electronic spectrum of the liquid and amorphous phases is a pseudogap at the Fermi level, which is consistent with the Nagel–Tauc electronic criterion of amorphous metallic alloy thermal stability.